PEDAGOGICAL OPPORTUNITIES OF TEACHING ENGLISH IN HIGHER EDUCATION BASED ON ARTIFICIAL INTELLIGENCE - Yertayeva Lazzat; Jakipbayeva Aigerim Rahatovna (Modern Scientific Method, 2026)
This article examines the pedagogical opportunities of integrating artificial intelligence (AI) into the process of teaching English in higher education institutions. The study focuses on the role of AI in developing language skills, its potential for personalizing instruction, and its impact on enhancing students’ cognitive engagement. The research is based on a descriptive-analytical methodology and includes a theoretical analysis of domestic and international studies in the fields of linguodidactics, pedagogy, and digital education. The findings indicate that the targeted application of AI, guided by didactic principles, increases the effectiveness of English language teaching. Moreover, AI is presented not as a tool to replace the teacher, but as a pedagogical resource that enriches the learning process.